2012
DOI: 10.1097/igc.0b013e31823c36b8
|View full text |Cite
|
Sign up to set email alerts
|

CD105/Ki67 Coexpression Correlates With Tumor Progression and Poor Prognosis in Epithelial Ovarian Cancer

Abstract: Our results suggest that the CD105 and Ki67 expressions might be involved in the progression of EOC and patient prognosis. A combined detection of CD105/Ki67 coexpression may benefit us in predicting the prognosis in EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Ziebarth et al demonstrated that forced ENG inhibition resulted in decreased cell viability, increased apoptosis, induced double-stranded DNA damage, and increased cisplatin sensitivity in ovarian cancer cell lines (50). In our study, ENG was upregulated in the wt TP53 cell lines and was a surprising finding given the association between increased ENG staining in MCV or tumor-associated endothelial cells and advanced stage disease, suboptimal cytoreduction (51), and increased disease progression (52, 53). There are conflicting results regarding the association between ENG and survival (51, 54, 55).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Ziebarth et al demonstrated that forced ENG inhibition resulted in decreased cell viability, increased apoptosis, induced double-stranded DNA damage, and increased cisplatin sensitivity in ovarian cancer cell lines (50). In our study, ENG was upregulated in the wt TP53 cell lines and was a surprising finding given the association between increased ENG staining in MCV or tumor-associated endothelial cells and advanced stage disease, suboptimal cytoreduction (51), and increased disease progression (52, 53). There are conflicting results regarding the association between ENG and survival (51, 54, 55).…”
Section: Discussionmentioning
confidence: 55%
“…There are conflicting results regarding the association between ENG and survival (51, 54, 55). High ENG expression in combination with high transforming growth factor B levels prior to chemotherapy have been associated with improved overall survival (55) while others have reported either decrease survival for those with the highest levels of ENG expression (51, 53) or no relationship at all (54). Previously, we used ENG staining to determine MVD.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is essential for cell proliferation (Liu et al, 2012). Ki-67 is required for the synthesis of ribosomes during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies the relationship between MVD (by using CD105 marker) and factors such as metastasis, Stage of tumor, proliferation rate of tumor cells and survival has been investigated (Liu et al, 2012), but in salivary gland tumors, the association between this factor and tumor cell proliferation rate has not been studied, therefore this study was based on investigating the relationship between these two factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ki67 was identified as an important prognostic factor for many tumor entities with respect to chemosensitivity and disease recurrence/death (Falato et al 2014;Li et al 2016;Rowe et al 2016). Its prognostic value in ovarian carcinoma remains controversial (Liu et al 2012;Masoumi-Moghaddam et al 2015;Feng et al 2016;Green et al 2016) and its correlation with VASH1 is not well known. The present study demonstrated that the high Ki67 expression group had a good prognosis but that there were no significant differences.…”
Section: Discussionmentioning
confidence: 99%